Animal Patents
XIV, 369 p.
Keywords: Following the US Patent Office's announcement in 1987 that it considers animals "to be patentable subject matter within the scope" of patent laws, there has been worldwide debate on this subject. This work comprises the proceedings of the Animal Patents Symposium 1988 at Cornell University.